Voice Handicap Index: European Portuguese versions, validity, and usefulness - Guimarães, Isabel (2023)
Aims: With regard to Voice Handicap Index (VHI) in European Portuguese the aims are to: (i) Identify the versions in use; (ii) Analyse the linguistic-cultural adaptation process used and the clinimetric properties and (iii) Determine the clinical and scientific usefulness.  Study design: Systematic literature review.  Material and Methods: Two independent researchers searched the databases, open access repositories and the archives of two portuguese scientific journals. Clinimetric properties, and clinical and scientific usefulness analysis was performed following the international guidelines for patient reported outcome measurements (PROMs). Results: In total, five questionnaires were identified in EP, the original VHI, the reduced versions VHI-9i, VHI-10 and the adapted versions - pediatric (pVHI) and for singers (SVHI). The VHI is unique in providing evidence of the ten recommended clinimetric properties. Conclusions: VHI is recommended to be used in assessment and research while the others have the potential to be recommended.